TOKOH BELLE DAN FEMINISME DALAM FILM BEAUTY AND THE BEAST 2017 - Melitasari, Indriana; Sugiarica Joni, I Dewa Ayu; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium, 2019)
ABSTRACT   Film is one of the mass media that provides the reality through the code and particular symbol in audio-visual form. The representation of reality presented in a film tends to influence the viewers’ understanding toward reality. Film does not merely have a positive effect, many films also contain the representation of gender inequality. One of them is Disney Princess Fairy Tales. Disney film progressively receives the critics from the feminists since it represents a passive Princess that relies on the Prince’s help. Responding to the critics, Disney eventually presents the different Princess figure which is tougher. Thus, this research aims to explain the representation of feminism in the film entitled Beauty and Beast 2017. This research used qualitative study approach and interpretive constructivist paradigm employing the analysis method of Peirce’s semiotics. The result of the study shows that feminism representation reflected in the figure of Belle is the postmodern feminism since Belle focuses more on showing her existence as a woman by being herself. Belle’s postmodern feminism is reflected by her intelligent characteristic, bravery in opposing the man’s view, tough and brave attitude, decisive figure as well as the presence of gender equity in a film.   Keywords : Disney film, Postmodern feminism, Representation,Semiotics